Changes in Heart Rate Variability and Glycosylated Hemoglobin in Prediabetics and Type 2 Diabetes Mellitus - Mishra, A.K.; Jha, R.K.; Kapoor, B.K. (Journal of Advances in Internal Medicine, 2017)
Background People with diabetes mellitus (DM) suffer from cardiac autonomic neuropathy (CAN), this may remain subclinical and reduced heart rate variability (HRV) is noticed as its early indicator. Objective The present study was undertaken to investigate the changes in heart rate variability and glycosylated hemoglobin (HbA1C) in (i) pre-diabetics, (ii) diabetics, (iii) non-diabetic subjects. Methods The present study enrolled 30 patients, diagnosed with type 2 DM and 30 prediabetic subjects aged between 30-60 years and compared with its aged matched healthy controls. In HRV, Time Domain (TD) parameters used were: SDNN, rMSSD, NN50 and pNN50%; and Frequency Domain (FD) parameters were: low frequency (LF), high frequency (HF) and LF/HF ratio. Glycosylated Hb and random blood sugar were measured. Results In HRV, though the time domain measures that reflects parasympathetic activity decreased was insignificant in the cases, the FD parameters such as LF reflecting activities of both division of ANS and HF reflecting only parasympathetic activity were found significantly reduced in diabetes and then control, whereas LF/HF ratio was increased only in diabetic patient (p<0.001) indicating sympathovagal imbalance. Rise in HbA1C was insignificant in prediabetic compared to control, which was observed significant only in diabetic (p< 0.001) patients. Conclusion Findings of the present study suggest that though HbA1c is an indicator of sustained hyperglycemia for monitoring glycemic level, even before its significant rise in plasma, alteration of sympatho-vagal balance over heart begins early in the disease process of diabetes. Journal of Advances in Internal Medicine 2016;05(01):15-18